HUBUNGAN ANTARA MOTIVASI BERPRESTASI DAN IKLIM SEKOLAH DENGAN HASIL BELAJAR KOMPUTER AKUNTANSI DI SEKOLAH MENENGAH KEJURUAN NEGERI WILAYAH JAKARTA PUSAT I - Yanuar Kusnendar; Ernawati Ernawati; Elin Driana (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to determine the relationship between Achievement Motivation and School Climate with Computer Accounting Learning Outcomes in State Vocational High Schools in Central Jakarta I Region. This type of research is a causal qualitative research that measures the relationship of independent variables to the dependent variable. The population in this study were students of the State Vocational High School in Central Jakarta Region I as many as 180 students. The research sample amounted to 115 students taken by random sampling technique using the slovin method. Data testing using the SPSS test tool with multiple linear regression testing after passing validity and reliability testing. The results showed that partially there is a significant relationship between achievement motivation and student learning outcomes, there is a significant relationship between school climate and student learning outcomes and there is a significant relationship between achievement motivation, school climate and student learning outcomes together